Strategi Pencapaian Kesetaraan Gender Dalam Rumah Tangga Nelayan - Muhammad Bibin; Nurul Purnomo; Ani Ardian; Sry Iin Indirwan; Saman Gita Marewa (Jurnal Ilmu Sosial dan Humaniora, 2024)
Decision-making in a household should not be done single-handedly by the husband as the head of the family. However, it needs to involve the wife, who plays an important role in improving the family economy. Generally, the women or wives in Palopo had not been involved in decision-making and had not been fully supported by government programs taking sides with the women. This study sought to analyze gender equality of decision-making in fisherman households and formulate a priority strategy for achieving gender equality in these households. Data collection was done using observation and structured interviews using questionnaires addressed to 7 stakeholders consisting of government agency officials, the Chair of Fisherman Cooperative, the Head of Nasyiah, and the Head of the Fisherman Group, as well as 30 families (husband and wife) whose livelihood depended in the fishery sector. The Moser analysis and Analytical Hierarchy Process (AHP) were used to analyze the obtained data. This study revealed some results. The women or wives were responsible and more dominant as decision-makers in household, family, and financial matters. The men or husbands were responsible and more dominant decision-makers in production activities and social affairs. In addition, implementing outreach programs for coastal communities in Palopo had not been gender-responsive. Thus, the priority strategy in achieving gender equality in fisherman households, which holds the best opportunity and is considered important by stakeholders, is developing a guidance program for coastal communities, men, and women.